Relation of accommodative microfluctuation with dry eye symptoms in short tear break-up time dry eye. - Minako Kaido; Motoko Kawashima; Yuta Shigeno; Yoshiaki Yamada; Kazuo Tsubota (PLoS ONE)
Purpose To investigate accommodative microfluctuations (AMFs) and visual function in short tear break-up time (BUT)-type dry eye (DE) and non-DE subjects. Methods This prospective comparative study included 48 volunteers with DE symptoms (mean age 34.8 ± 5.5 years, age range 25-42 years) and 73 without DE symptoms (mean age 30.6 ± 4.7 years, age range 25-42 years). The eyes were divided into two groups: (1) DE group with DE symptoms and BUT ≤ 5 s and (2) non-DE group without DE symptoms and BUT > 5 s. We excluded eyes with Schirmer score ≤ 5 mm and positive keratoconjunctival epithelial damage. Tear evaluation, AMF, and functional visual acuity (VA) examinations were performed. AMF parameters included total high-frequency component (HFC), HFC with low accommodation for the task of staring into the distance (HFC1), and HFC with high accommodation for deskwork (HFC2). Functional VA parameters included starting VA, functional VA, visual maintenance ratio, and blink frequency. Results A total of 33 and 34 eyes were categorized in the DE and non-DE groups, respectively. Mean blink frequency and HFC1 values were significantly higher in the DE group than they were in the non-DE group. Conclusions DEs with symptoms showed abnormal AMF and visual function, which may be associated with DE symptoms.